ANALISIS HUBUNGAN ANTARA TIMOR LESTE DAN AUSTRALIA TERKAIT PEREBUTAN SUMBER DAYA MINYAK DAN GAS PADA SENGKETA CELAH TIMOR (TIMOR GAP) - Shana Lia Mifroh (JURNAL POLINTER : KAJIAN POLITIK DAN HUBUNGAN INTERNASIONAL, 2021)
In this journal, the author will explain on the Timor Gap in which there is involvement between East Timor and Australia. This research will explain the relationship between the two countries during the dispute, Indonesia's relationship as a country that is also involved, as well as the concept of diplomacy used to resolve this conflict. As well as triggering conflicts between countries that can grip the international world, sovereignty is said to have always been part of an international issue, since sovereignty is really crucial for a country. Moreover, in the Timor Gap dispute there are contested resources that are oil and gas that are very profitable for the prosperity and well-being of the country. The natural wealth that settles in the Timor Sea makes countries around the East East participate in the utilization of these resources, thus giving cooperation between each country because of its involvement. Thus, the focus of the discussion in this journal will show how the relationship built between the two countries concerns the struggle for natural resources in the Timor Gap. This research also uses a qualitative approach as a research method and is supported by the data that has been collected.